The Intrinsic Value of Family Temple Construction in Kasimbar Sub-District - Angriana T Winter; Chalarce Totanan; Rahma Masdar; Muhammad Din; Ni Made Suwitri Parwati; Betty (Yayasan Amerta Insan Unggul, 2025)
This research aims to find the interinsic value of the cost of building a family temple. The type of research is ethnographic approach. The data used is primary data collected through observation, interviews and documentation. The results found that the intrinsic value of family temple construction reflects deep spiritual, cultural, and social meanings for Hindus. The family temple not only functions as a place of worship to ancestors and manifestations of Ida Sang Hyang Widhi Wasa, but also a symbol of the strength of identity, identity, and emotional attachment between family members. In addition, the process of building a temple also fosters the spirit of mutual cooperation, togetherness, and sincere devotion to dharma values. Thus, the construction of a family temple is not just a physical activity, but a manifestation of the sacred intention to maintain spiritual harmony in family and community life. Theoretically, the development of science has a significant impact on understanding the meaning of intrinsic values in the construction of family temples. The development of science helps to interpret these values not just as part of tradition, but as a foundation that strengthens the family's cultural and spiritual identity. Thus, a broader understanding of intrinsic values through scientific studies encourages people to build family temples not only as physical structures, but as centers of value, moral and spiritual development that have a long-term impact on the family's cultural and social resilience.